SIGNIFICANCE OF MASTERING SPECIALIZED VOCABULARY IN ECONOMICS IN DEVELOPING LEXICAL COMPETENCE OF B2 LEVEL LEARNERS - Inagamova Nargis Abdullayevna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This article emphasizes the significance of mastering specialized vocabulary in economics for B2 level learners in developing lexical competence. It highlights the importance of understanding and using specialized economic terminology such as "inflation," "supply and demand," and "marginal utility" in both academic and professional settings. The article discusses how mastering this vocabulary helps learners understand complex economic theories, engage in meaningful discussions, and succeed in professional environments. It also explores the role of digital technologies in enhancing vocabulary acquisition and provides examples of tools that facilitate this learning process. Ultimately, the article illustrates the importance of specialized vocabulary in achieving academic success and career advancement for economics students.